Pendidikan dan Pelatihan Tata Kelola Koperasi Modern - Wahyudin Wahyudin (LPPM Universitas Koperasi Indonesia, 2023)
One of the problems that hinder cooperatives from progressing and developing is the problem of human resources (HR). From the old management of the cooperative, the knowledge of cooperatives that is still lacking and the wrong business development makes the cooperative not develop even towards setbacks and failures. Until now one of the cooperative problems is still the same, namely the problem of human resources besides the cooperative has not fully implemented the cooperative principles completely and correctly. Many cooperatives run their business the same as general companies, seek high profits, offer high loan interest and there is no difference in application between cooperative members and non-members. So that the benefits of being a cooperative member are not felt by the members. Cooperative education is important not only for administrators but also for cooperative members. This is important to foster a love for cooperatives as business entities owned by members and the willingness to carry out transactions in cooperatives to fulfill their needs. Without the knowledge of cooperatives for members, members will think that transactions are the same between transactions in cooperatives and outside cooperatives. Even though the progress of cooperatives is very dependent on the participation of cooperative members. Cultivation of cooperative capital will be better and will have healthy finances if more sources come from cooperative members. For the management of business development, it is important to promote and develop cooperatives. But of course, the development of this business must be feasible and in accordance with the needs of members. So it is very important and necessary for education and training for administrators and members of cooperatives to become modern cooperatives.